A laboratory system for modeling hay storage - Coblentz, W.K.; Fritz, J.O.; Bolsen, K.K. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
A simple system is described that uses a hinged metal baling unit and a hydraulic press to make 4.0 × 4.3 × 5.3 inch wire-tied, laboratory- scale, hay bales. A comparison of densities of conventional, small, alfalfa bales (15×18×37 inches) and laboratory bales was made over a wide range of moisture levels (15 to 36%) and conventional bale densities (10 to 25 lb/ft3). Laboratory bale densities were regressed against conventional bale densities and agreement was excellent. The system is inexpensive to build and easy to use and can be reproduced easily.
Keywords: Beef; Hay; Bale; Laboratory-scale; Alfalfa